Fire Ant Decapitating Flies Pseudacteon spp. (Insecta: Diptera: Phoridae) - Ariane McCorquodale; James P. Cuda; Sanford D. Porter (EDIS)
Previously published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/beneficial/flies/ant_decapitating_phorids.htm